A comparative evaluation of casein phosphopeptide-amorphous calcium phosphate and fluoride on the shear bond strength of orthodontic brackets - (:unkn) unknown (OXFORD UNIV PRESS, 2011)
The purpose of the study was to evaluate and compare the effects of topical application of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and fluoride on the shear bond strength (SBS) of orthodontic brackets bonded to human premolar teeth. Eighty extracted human premolar teeth were cleansed of soft tissue, then polished with non-fluoridated pumice, and immersed in water for 1-3 months until testing. The teeth were randomly divided into four groups: group 1, control, without pre-treatment of the enamel; group 2, the enamel was treated with 5 per cent sodium fluoride varnish for 4 minutes; group 3, the enamel was treated with CPP-ACP for 3 minutes; and group 4, the enamel was treated with 5 per cent sodium fluoride and CPP-ACP. All bonded specimens were immersed in distilled water at room temperature for 24 hours and subsequently tested for SBS in a universal testing machine. After debonding, the bracket bases and the enamel surfaces were examined by eye to assess any adhesive remaining, in accordance with the Adhesive Remnant Index (ARI). Descriptive statistics were calculated for each group. Analysis of variance and Tukey honestly significant difference (HSD) test were performed to compare the SBS of the groups. The chi-square test was used to evaluate differences in ARI scores between the groups. The SBS in group 2 was significantly lower than groups 1, 3, and 4 (P < 0.001). ARI scores were not significantly different between the four groups (P > 0.05). CPP-ACP, either alone or combined with fluoride, may safely be used as a prophylactic agent before bracket bonding.
Keywords: PHOSPHATE/METHACRYLATE COMPOSITES; MECHANICAL-PROPERTIES; BOVINE ENAMEL; IN-VITRO; CPP-ACP; CARIES; ADHESIVE; VARNISH; LESIONS; SYSTEM